Preferensi Konsumen Bawang Merah Goreng PT Permata Indah Rubaru (PIR) untuk Mengetahui Keputusan Pembelian - Winarsih, Nuriyana; Hayati, Mardiyah; Zuhriyah, Amanatuz (Journal of Agribusiness Science and Rural Development, 2024)
The large number of competitors selling similar fried shallot products has an influence on PT PIR's sales of fried shallots. To increase sales, producers must know the tastes that consumers prefer. This research aims to determine the characteristics of consumers of PT PIR's fried shallots, determine the combination of attributes of PT PIR's fried shallots that consumers like, and determine consumer preferences based on the attributes consumers consider in determining purchasing decisions PT PIR fried shallots. The sampling technique in this research used Accidental Sampling with an analysis method using conjoint analysis. The research results show that the characteristics of PT PIR's fried shallot consumers are mostly women aged 21-30 and 31-40 years, 16 years of education, self-employed, income (per month) IDR 1,500,000 - IDR 3,000,000, expenses (per month) IDR 500,000 - IDR 1,500,000, as well as offline purchasing behavior. The combination of attribute levels chosen by consumers is PT PIR fried shallots, snack type, original taste, price 17,000, crunchy texture mixed with flour, golden yellow color, weight 100 grams, shelf life 8 months, pouch packaging form, and place of purchase at supermarkets. The order of attributes considered by consumers is taste, price, place of purchase, packaging form, weight, type, texture, durability and color.